Peningkatan Pengetahuan dan Keterampilan Perangkat Desa Di Wilayah Kabupaten Mojokerto Terhadap PBG/SLF Sesuai PP No. 21 Tahun 2022 - Sarasanty, Diah; Asmorowati, Erna Tri; Nurcahyanto, Akbar Rizky; Cahyadi, Rizal (Maslahah: Jurnal Pengabdian Masyarakat, 2024)
It is impossible to resist the growth of building construction in the Mojokerto City and Regency as a PKN (National Activity Support) area. All parties involved, though, need to approach this objectively in order to ensure that building development continues to adhere to the RTRW and maintain user comfort, safety, and health. Therefore, the government has set up a licensing system through https://simbg.pu.go.id/ to facilitate building permits. Offering technical advice on building construction in the Mojokerto City and Regency region is the goal of this activity. The 12-month duration of this activity is set for January 2023 to December 2023. Publication in community service journals and community education initiatives on the PBG/SLF procedure are the anticipated results.